2002
DOI: 10.1093/hmg/11.21.2559
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the signal peptide region of the bicistronic gene DSPP affects translocation to the endoplasmic reticulum and results in defective dentine biomineralization

Abstract: Dentine dysplasia type II is an autosomal dominant disorder in which mineralization of the dentine of the primary teeth is abnormal. On the basis of the phenotypic overlap between, and shared chromosomal location with, dentinogenesis imperfecta type II, a second disorder of dentine mineralization, it has been proposed that the two conditions are allelic. As recent studies have shown that dentinogenesis imperfecta type II results from mutation of the bicistronic dentine sialophosphoprotein gene (DSPP ), we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
115
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 23 publications
3
115
0
1
Order By: Relevance
“…So far, it has been reported that the p.Y6D mutation in the signal peptide prevents the translocation of the mutated N-terminal DSP fragment into the ER in vitro. (20) Mutations in exons 2 and 3 were preliminarily reported to cause retention of the protein to the ER, (21) in line with the presumed impairment of signal peptide cleavage. However, whether any of these mutations have wider effects on ER function or protein export has not been clarified.…”
Section: Discussionmentioning
confidence: 98%
“…So far, it has been reported that the p.Y6D mutation in the signal peptide prevents the translocation of the mutated N-terminal DSP fragment into the ER in vitro. (20) Mutations in exons 2 and 3 were preliminarily reported to cause retention of the protein to the ER, (21) in line with the presumed impairment of signal peptide cleavage. However, whether any of these mutations have wider effects on ER function or protein export has not been clarified.…”
Section: Discussionmentioning
confidence: 98%
“…56 Description of DSPP mutation in a patient affected by DD-II confirmed this hypothesis and explained these clinical similarities. 57 Towards a nosology defined by mutations spectrum To date 38 pathological variants have been described in the DSPP gene, located in the peptide signal region, within the DSP region and within the DPP region (Table 2). 1,7,28,43,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Most of them (28) leads to DGI-II, eight to DD-II and two to DGI-III.…”
Section: Dentin Dysplasia Type I or Radicularmentioning
confidence: 99%
“…Extensive evidence indicates that DSPP plays a crucial role during both enamel and dentin biomineralization and/or the formation of the structural diversity of tooth layers (i.e., enamel, mantle dentin, predentin and orthodentin) (1,9,10). DSPP mutations are reported to be associated with DD-II, DGI-II (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and DGI-III (21), resulting in abnormal dentin formation. Furthermore, DSPP knockout mice display a widened predentin zone and develop defective mineralization similar to human dentinogenesis imperfecta III (22).…”
Section: Introductionmentioning
confidence: 99%